Urinary mycoestrogens and age and height at menarche in New Jersey girls - Zorimar Rivera-Núñez; Emily S. Barrett; Elizabeth A. Szamreta; Sue A. Shapses; Bo Qin; Yong Lin; Helmut Zarbl; Brian Buckley; Elisa V. Bandera (BMC, 2019)
Abstract Background Despite evidence of the endocrine disrupting properties of zearalenone (ZEN) and alpha-zearalanol (zeranol, α-ZAL), they have been minimally studied in human populations. In previous cross-sectional analyses, we demonstrated that 9-10 years old girls with detectable urinary ZEN were of shorter stature and less likely to have reached the onset of breast development than girls with undetectable urinary ZEN. The aim of this study was to examine baseline concentrations of ZEN, (α-ZAL), and their phase-1 metabolites in relation to subsequent growth and timing of menarche using 10 years of longitudinal data. Methods Urine samples were collected from participants in the Jersey Girl Study at age 9-10 (n = 163). Unconjugated ZEN, (α-ZAL), and their metabolites were analyzed using high performance liquid chromatography and tandem mass spectrometry. Information on height, weight, and pubertal development was collected at a baseline visit with annual follow-up by mail thereafter. Cox regression was used to evaluate time to menarche in relation to baseline ZEN, (α-ZAL), and total mycoestrogen exposure. Z-scores for height and weight were used in mixed models to assess growth. Results Mycoestrogens were detectable in urine in 78.5% of the girls (median ZEN: 1.02 ng/ml, range 0-22.3). Girls with detectable urinary concentrations of (α-ZAL) and total mycoestrogens (sum of ZEN, (α-ZAL) and their metabolites) at baseline were significantly shorter at menarche than girls with levels below detection (p = 0.04). ZEN and total mycoestrogen concentrations were inversely associated with height- and weight-z-scores at menarche (adjusted β = − 0.18, 95% CI: -0.29, − 0.08, and adjusted β = − 0.10, 95% CI: -0.21, 0.01, respectively). Conclusion This study supports and extends our previous results suggesting that exposure to ZEN, (α-ZAL), and their metabolites is associated with slower growth and pubertal development in adolescent girls.